A Comparative Analysis of European Time Transfers between Generations and Genders - Zagheni, Emilio. author. aut Link
X, 48 p. 21 illus., 20 illus. in color.
Keywords: This comparative study of European time transfers reveals the full extent of transfers in the form of unpaid work and highlights the existence of important gender differences in household time production. A large quantity of goods and services are produced by household members for their own consumption, without involving market transactions. Despite the economic and social importance of unpaid work, these productive activities are largely invisible to traditional national economic accounts. As a consequence, standard measures of intergenerational transfers typically ignore household production, and thus underestimate the overall value of goods and services produced over the life cycle; in particular, the economic contribution of females. The book uses a life course approach to offer policy-relevant insights into the effect of demographic and social change on intergenerational ties and gender inequality in household production.